2021
DOI: 10.1292/jvms.21-0177
|View full text |Cite
|
Sign up to set email alerts
|

First report of ophidiomycosis in Asia caused by <i>Ophidiomyces ophiodiicola</i> in captive snakes in Japan

Abstract: Ophidiomycosis is an emerging infectious disease caused by the fungus Ophidiomyces ophiodiicola, which has been affecting wild and captive snakes in North America, Europe, and Australia. We report 12 cases of suspected ophidiomycosis in captive colubrid snakes in Japan. Pathological and microbiological examinations were performed, and the results confirmed the diagnosis of ophidiomycosis in two snakes, which indicated that the remaining sympatrically raised snakes also had ophidiomycosis since they exhibited s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Ophidiomycosis is known to affect wild snake populations in North America (Chandler et al 2019, Licitra et al 2019, Allender et al 2020, Haynes et al 2020), and its presence has also been confirmed in Europe (Franklinos et al 2017, Meier et al 2018, Blanvillain et al 2022) and Asia (Grioni et al 2021, Sun et al 2021). The disease has also been demonstrated in captive snakes in Europe (Vissiennon et al 1999, Picquet et al 2018), Asia (Takami et al 2021), North America (Nichols et al 1999, Bertelsen et al 2005, Steeil et al 2018) and Australia (Sigler et al 2013, WHA Fact Sheet 2021). The most important cause of the worldwide spread of fungal diseases, and a likely cause of the spread of ophidiomycosis, is the animal trade (Allender et al 2015b, Schillinger et al 2023).…”
Section: Introductionmentioning
confidence: 97%
“…Ophidiomycosis is known to affect wild snake populations in North America (Chandler et al 2019, Licitra et al 2019, Allender et al 2020, Haynes et al 2020), and its presence has also been confirmed in Europe (Franklinos et al 2017, Meier et al 2018, Blanvillain et al 2022) and Asia (Grioni et al 2021, Sun et al 2021). The disease has also been demonstrated in captive snakes in Europe (Vissiennon et al 1999, Picquet et al 2018), Asia (Takami et al 2021), North America (Nichols et al 1999, Bertelsen et al 2005, Steeil et al 2018) and Australia (Sigler et al 2013, WHA Fact Sheet 2021). The most important cause of the worldwide spread of fungal diseases, and a likely cause of the spread of ophidiomycosis, is the animal trade (Allender et al 2015b, Schillinger et al 2023).…”
Section: Introductionmentioning
confidence: 97%
“…Population genetic studies of Oo suggest multiple recent introductions of the fungus into North America, from an as yet unsampled source population 7 . Historical detections of the disease in captive snakes on multiple continents raises the possibility that transport of snakes may have been involved in inadvertent Oo introductions 7 9 . The disease typically leads to skin lesion formation with variable characteristics (e.g., crusting, erosion, ulceration, granuloma formation) and severity of presentation 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Ophidiomyces ophidiicola is a generalist fungus and is known to infect a wide range of snake species with different life histories, irrespective of taxonomy or habitat (Burbrink et al., 2017). Ophidiomycosis has been documented in more than 30 species of wild snakes in the United States and Europe (Lorch et al., 2016), with reported instances in Australia (Sigler et al., 2013) and Southeast Asia (Sun et al., 2022; Takami et al., 2021). Ophidiomycosis was first reported in the United States in the mid‐2000s but was likely present as early as the 1940s (Allender et al., 2011; Clark et al., 2011; Lorch et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Ophidiomycosis has been documented in more than 30 species of wild snakes in the United States and Europe (Lorch et al, 2016), with reported instances in Australia (Sigler et al, 2013) and Southeast Asia (Sun et al, 2022;Takami et al, 2021). Ophidiomycosis was first reported in the United States in the mid-2000s but was likely present as early as the 1940s (Allender et al, 2011;Clark et al, 2011;Lorch et al, 2021).…”
mentioning
confidence: 99%